Total Serum Testosterone Level in Obese Patients with Type -2 Diabetes Mellitus: Life Sciences-Medicine - Fatima Elhajhamad Mohamed-Khier; Shaza Elawad Sideeg; Nisreen Daffa Alla; Rehab Mustafa Badi (International Journal of Life Science and Pharma Research, 2022)
Both obesity and type 2 diabetes mellitus (T2DM) are independently associated with reduced serum testosterone. The additive effect of obesity and T2DM on reducing testosterone levels need to be investigated. Their combined additive effects may place obese T2DM patients at higher risk of decreased testosterone and the associated increased morbidity and mortality. The aim of this study was to screen obese T2DM patients for biochemical hypogonadism regardless of the presence of overt clinical symptoms to consider testosterone replacement therapy. 152 adult male aged 40 to 68 years with T2DM were recruited through simple random sampling. The study participants were grouped based on their BMI into lean (n=48); overweight (n=57), obese (n=37) and morbidly obese (n=11). Total serum testosterone (TST), BMI and waist circumference (WC) were measured in all patients and luteinizing hormone (LH) was measured in 103 of them. Low TST was defined as TST<9nmol/L and the normal range for LH was 1.7-11.2mIU/ml. Mean TST in lean T2DM patients was 15.61± 6.0 nmol/l. TST levels were significantly lower in obese and morbidly obese groups compared with the lean group (P=0.003 and 0.015 respectively). TST negatively correlated with BMI (r= -0.29, P<0.001) and WC (r= -0.21, P<0.009). Overall, 19.7% of T2DM patients had low TST. The prevalence of low TST increased from 14.9% in lean, to 21.1% in overweight, to 21.6% in obese, to 27.3% in morbidly obese T2DM patients, (P=0.74). LH was inappropriately normal in 95% (19/20) of patients with low TST. Obese T2DM patients had reduced TST levels and a higher prevalence of reduced TST compared to lean patients. TST negatively correlated with BMI and WC. Therefore, screening obese T2DM patients for testosterone deficiency should be considered.